Structural requirements for antigen presentation by mouse CD1 - Burdin, Nicolas (The National Academy of Sciences, 2000)
The structural basis for the T cell response to glycolipid antigens (Ags) remains poorly understood. T lymphocytes autoreactive for mouse CD1 (mCD1.1) or reactive for the glycosphingolipid αgalactosylceramide (α-GalCer) presented by mCD1.1 have been described previously. In this paper it is shown that mutations at the top of the α helices and in the bottom of the Ag-binding groove can disrupt both mCD1.1 autoreactivity and α-GalCer recognition. The locations of the positions that affect T cell responses indicate that recognition of mCD1.1 is not likely to be unconventional or superantigen-like. Furthermore, the effects of the bottom of the pocket mutation suggest that the autoreactive response could require an autologous ligand, and they indicate that α-GalCer binds to the groove of mCD1.1, most likely with the shorter 18-carbon hydrophobic chain in the A′ pocket. Natural killer T cell hybridomas with identical T cell antigen receptor (TCR) α chains and different β chains respond differently to α-GalCer presented by mCD1.1 mutants. This finding indicates a role for TCR β in defining natural killer T cell specificity, despite the more restricted diversity of the α chains in these cells. Overall, the data are consistent with a mode of lipoglycan recognition similar to that proposed for glycopeptides, in which the TCR α and β chains survey a surface composed of both mCD1.1 and the carbohydrate portion of α-GalCer.